1995
DOI: 10.1002/j.1552-4604.1995.tb04095.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of Food on Absorption of Cefpodoxime Proxetil

Abstract: The effect of a high-fat meal and the timing of this meal on the absorption of a 400-mg oral dose of cefpodoxime proxetil was evaluated in 20 healthy, adult, male volunteers in a four-way crossover study. The area under the plasma concentration-time curve, peak plasma concentration, and urinary recovery were significantly greater (P = .0001) after administration of cefpodoxime proxetil tablets with and 2 hours after a meal relative to dosing under fasted conditions or 1 hour before a meal. The time to peak con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Administration 1 and 2 hours after breakfast reduced relative bioavailability to about 45% of that from the fasted state. Borin et al 15 reported similar cefpodoxime plasma concentration-time profiles when this cephalosporin was administered both fasting and 1 hour before a high-fat breakfast meal. But unlike tacrolimus and didanosine, cefpodoxime plasma concentrations increased~1.4-fold (concomitant with a slightly longer t max ) when the drug was administered either with a meal or 2 hours following a meal.…”
Section: Effect Of Meal Consumption On Tacrolimus Dosementioning
confidence: 89%
“…Administration 1 and 2 hours after breakfast reduced relative bioavailability to about 45% of that from the fasted state. Borin et al 15 reported similar cefpodoxime plasma concentration-time profiles when this cephalosporin was administered both fasting and 1 hour before a high-fat breakfast meal. But unlike tacrolimus and didanosine, cefpodoxime plasma concentrations increased~1.4-fold (concomitant with a slightly longer t max ) when the drug was administered either with a meal or 2 hours following a meal.…”
Section: Effect Of Meal Consumption On Tacrolimus Dosementioning
confidence: 89%
“…Food has been shown to alter cefpodoxime bioavailability from tablets by increasing the extent of absorption of cefpodoxime proxetil (2,8). This food effect was not associated with meal composition because the increases in cefpodoxime bioavailability were similar in five equicaloric test meals which varied with respect to fat and protein content (8).…”
mentioning
confidence: 99%
“…However, by increasing their lipophilicity, their aqueous solubility was reduced, thus being classified in group IV of the BCS (Biopharmaceutical Classification System). The higher the dose of CP prescribed, the greater the benefit of taking it with a meal [39,40].…”
Section: Molecule T Max On Uneaten (H) T Max During Meal (H)mentioning
confidence: 99%